An Unveiling the Enigma: Case Series of Retroperitoneal Tumors and literature review - Purkayastha, Pallabi; Das, Rama; Das, Rhituparna (Tropical Journal of Pathology and Microbiology, 2025)
Introduction: Retroperitoneal tumours (RPTs) are a diverse group of lesions that arise in the retroperitoneum and pelvic space. The histological spectrum of retroperitoneal masses is broad, ranging from major aggressive malignancies to benign lesions. Objective: This case series and literature review aimed to study the incidence of retroperitoneal tumours presenting in a diverse array encountered in clinical practice, diagnosed on cytology or biopsy.